STRUCTURALISM OF TODOROV'S SEMIOTICS IN THE MOVIE "HACKSAW RIDGE" DIRECTED BY MEL GIBSON - Benny Dele Bintang Ananta; Muhammad Firza Thoriq Sholahuddin (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research discusses the structuralism of Todorov's semiotics in the movie "Hacksaw Ridge" directed by Mel Gibson. Structuralist studies have been abandoned for a long time. This study aims to determine the implementation of semiotic aspects of Todorov structuralism in films. A descriptive-qualitative method was used to analyze the data, and note-taking with Nvivo 12 software was used as the data collection technique. This study required a long process and knowledge of data analysis, which required importing, transcript, reducing, presenting and drawn conclusion. The findings examined the syntactical aspects of the 38 sequences found, including the form of words, events, characters, and verbal aspects, including mode, kala, point of view, and storytelling. This study concludes that film can be implemented in structured narrative and structuralism studies based on the Todorov model. This research has important implications for providing a deeper understanding of films’ creative excellence, thematic significance, and potential emotional impact.